Forty years of increasing suicide mortality in Poland: Undercounting amidst a hanging epidemic? - Höfer Peter; Rockett Ian R H; Värnik Peeter; Etzersdorfer Elmar; Kapusta Nestor D (BMC, 2012)
Abstract Background Suicide rate trends for Poland, one of the most populous countries in Europe, are not well documented. Moreover, the quality of the official Polish suicide statistics is unknown and requires in-depth investigation. Methods Population and mortality data disaggregated by sex, age, manner, and cause were obtained from the Polish Central Statistics Office for the period 1970-2009. Suicides and deaths categorized as 'undetermined injury intent,' 'unknown causes,' and 'unintentional poisonings' were analyzed to estimate the reliability and sensitivity of suicide certification in Poland over three periods covered by ICD-8, ICD-9 and ICD-10, respectively. Time trends were assessed by the Spearman test for trend. Results The official suicide rate increased by 51.3% in Poland between 1970 and 2009. There was an increasing excess suicide rate for males, culminating in a male-to-female ratio of 7:1. The dominant method, hanging, comprised 90% of all suicides by 2009. Factoring in deaths of undetermined intent only, estimated sensitivity of suicide certification was 77% overall, but lower for females than males. Not increasing linearly with age, the suicide rate peaked at ages 40-54 years. Conclusion The suicide rate is increasing in Poland, which calls for a national prevention initiative. Hangings are the predominant suicide method based on official registration. However, suicide among females appears grossly underestimated given their lower estimated sensitivity of suicide certification, greater use of "soft" suicide methods, and the very high 7:1 male-to-female rate ratio. Changes in the ICD classification system resulted in a temporary suicide data blackout in 1980-1982, and significant modifications of the death categories of senility and unknown causes, after 1997, suggest the need for data quality surveillance.